Penerapan Metode Picture And Picture Untuk Meningkatkan Kemampuan Berhitung Siswa Kelas II SD Negeri 01 Mamben Daya - Jupriadi; Misrahuddin; Muhamad Akrom (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
This study aims to determine the effect of applying the picture and picture method to improve the numeracy skills of grade II students at SD Negeri 01 Mamben Daya for the 2022/2023 academic year. The research subjects were grade II students at SD Negeri 01 Mamben Daya with a total of 31 students consisting of 17 boys and 14 girls. The results of this study indicate that the results of the evaluation using a written test in the form of multiple choices to find out the acquisition of students' numeracy skills are quite good, namely from the first cycle the results were 64%, which then increased by 20% so that the proportion of completeness in the second cycle became 84% with an average class cycle I of 64 which then increased in cycle II to 84. Thus the application of the picture and picture method to improve numeracy skills in class II students at SD Negeri 01 mamben daya for the 2022/2023 academic year can improve participants' numeracy skills educate.